Development of brown coal porosity under thermolysis with alkalis of different nature - Tamarkina, Yu. V.; Bovan, L. A.; Tsyba, N. N.; Kucherenko, V. A. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2008)
A comparison has been made of porous structure characteristics of thermolysis (800°С, 1 h) solid products from Aleksandria brown coal (BC) and “BC-MOH” (М=Li, Na, K) compounds prepared by impregnation of coal with alkali metal hydroxide aqueous solution. Porous structure characteristics were calculated by different methods basing on data of low-temperature (77 К) adsorption-desorption nitrogen isotherms. Hydroxides MOH were found to promote adsorbent porosity development; total pore volume increase with increasing cation diameter. In alkali presence, ~ 4 nm diameter pores are mostly developed and this effect becomes more evident in a row of alkali LiОН < NaОН < KОН. Potassium hydroxide promotes micropore (≤ 2 nm) development, LiОН and NaОН – inhibit it. КОН is the most effective reagent for brown coal conversion into adsorbents.